Integrated Control of Powdery Mildew Using UV Light Exposure and OMRI-Certified Fungicide for Greenhouse Organic Lettuce Production - Arash Ghalehgolabbehbahani; Gladis Zinati; Said Hamido; Nikita Bhusal; Madhav Dhakal; Reza K. Afshar; Jean B. Contina; Romans Caetani; Andrew Smith; Dinesh Panday (Horticulturae)
Lettuce (Lactuca sativa L.) is a widely cultivated crop due to its short production cycle and high market demand. However, powdery mildew (Golovinomyces cichoracearum) poses a significant threat, reducing yields by up to 30% in various lettuce cultivars. This greenhouse study, conducted at the Rodale Institute in Pennsylvania, evaluated the impacts of pre-transplant UV light exposure and post-planting application of an OMRI-certified fungicide, potassium bicarbonate (MilStop), on powdery mildew infestation, yield, and nutritional quality of lettuce. The treatment included three factors: (a) UV-B (280 to 315 nm) exposure: treated vs. non-treated, (b) UV-C (100 to 280 nm) exposure: treated vs. non-treated, and (c) fungicide application: treated vs. non-treated, arranged in a factorial randomized complete block design with four replications. Lettuce seedlings (Salanova cultivar) were exposed to UV light before transplanting and later treated with MilStop. The results indicated that the combination of UV-B and MilStop significantly reduced powdery mildew infestation, while UV-C alone showed no significant effect. MilStop application enhanced lettuce yield, with treated plots showing a 44.8% increase in harvestable weight over control plots. While mineral and monosaccharide content were unaffected, UV-B exposure significantly increased total amino acid concentrations, including essential and non-essential amino acids. Pearson’s correlation analysis revealed a strong negative relationship between powdery mildew severity and harvestable weight, highlighting the importance of disease management. These findings highlight the potential of integrating UV light treatments and fungicide applications as effective, sustainable strategies for managing powdery mildew, improving lettuce yield, and maintaining nutritional quality in regenerative organic systems.